Nacionalismo musical e brasilidade: uma revisão - Frungillo, Mário D [UNESP] (2014)
The main objective of this study was to investigate the musical nationalism in Brazil and what role he had in relation to possible progress or setbacks in the history of Brazilian music during the early twentieth century until the 1960s. From the survey of essential concepts as culture, identity, nation and nationalism, I focused the unfolding of the Semana de Arte Moderna (Week of Modern Art) in 1922 and the publication of the Ensaio sobre a música brasileira (Essay on Brazilian music), Mário de Andrade, in 1928, in which he exposes a program for the configuration of classical brasilian music. Through a qualitative analysis of texts and significant events I sought to identify the conceptions and manifestations of nationalism and Brazilianness, understand their connections and reassess the periodization of Brazilian music